Computer Forensic Using Photorec for Secure Data Recovery Between Storage Media: a Proof of Concept - Pratama, I Putu Agus Eka (International Journal of Science, Technology & Management, 2021)
Data plays the important role, so that data recovery and data security be prioritized. Computer users often lose their data due to personal errors or by attacks. Digital forensics has one sub-field called computer forensic, which has an important role in the process of secure data recovery. USB Flashdisk as the most widely used storage media has a probability of data loss. It is necessary to do computer forensic actions, especially secure data recovery, on it so that it can restore data securely to other media while protecting it by giving privilege root. In this research, computer forensic testing the 2781 files of various data formats that were erased on a 32 GB USB flash drive using Photorec. The media for collecting data recovery results using an Intel computer, 2 GB RAM, 1.8 GHz processor, the Linux operating system Xubuntu 20.04. Testing is carried out following the test scenarios that have been designed, then observed, recorded, and analyzed. Photorec places recovery data in 6 recup_dir subdirectories. Test results and analysis of the test results show that Photorec is a reliable tool for computer forensic, especially secure data recovery because it can restore 100% of data, accompanied by privilege root for all data recovery results, so they cannot be changed and deleted by an end-user without granted access.